Neuromuscular activity of upper and lower limbs during two backstroke swimming start variants - De Jesus, K.; De Jesus, K.; Medeiros, A. I. A.; Goncalves, P.; Figueiredo, P.; Fernandes, R. J.; Vilas-Boas, J. P. (Journal of Sports Science & Medicine, 2015)
A proficient start is decisive in sprint competitive swimming events and requires swimmers` to exert maximal forces in a short period to complete the task successfully. The aim of this study was to compare the electromyographic (EMG) activity in-between the backstroke start with feet positioned parallel and partially emerged performed with the hands on the highest horizontal and on the vertical handgrip at hands-off, take-off, flight and entry start phases. EMG comparisons between starting variants were supported by upper and lower limb joint angles at starting position and 15 m start time data. Following a four-week start training to familiarize participants with each start variant, 10 male competitive backstroke swimmers performed randomly six 15 m maximal trials, being three of each start variant. Surface EMG of Biceps Brachii, Triceps Brachii, Rectus Femoris, Biceps Femoris, Gastrocnemius Medialis and Tibialis Anterior was recorded and processed using the time integral EMG (iEMG). Eight video cameras (four surface and four un-derwater) were used to determine backstroke start phases and joint angles at starting position. EMG, joint angles and temporal parameters have not evidenced changes due to the different handgrips. Nevertheless, clear differences were observed in both variants for upper and lower limb muscles activity among start-ing phases (e.g. Biceps Brachii at take-off vs. flight phase, 15.17% ± 2.76% and 22.38% ± 4.25%; 14.24% ± 7.11% and 25.90% ± 8.65%, for variant with hands horizontal and vertical-ly positioned, respectively). It was concluded that different handgrips did not affect EMG, kinematics and temporal profile in backstroke start. Despite coaches might plan similar strength training for both start variants, further attention should be given on the selection of proper exercises to maximize the contribution of relevant muscles at different starting phases.